2001
DOI: 10.1002/ps.394
|View full text |Cite
|
Sign up to set email alerts
|

The hydroxyanilide fenhexamid, a new sterol biosynthesis inhibitor fungicide efficient against the plant pathogenic fungus Botryotinia fuckeliana (Botrytis cinerea)

Abstract: Fenhexamid, a recently developed botryticide, is shown here to inhibit sterol biosynthesis. When the fungus Botryotinia fuckeliana was grown in the presence of fenhexamid, the ergosterol content was reduced, and three 3-keto compounds, 4 alpha-methylfecosterone, fecosterone and episterone, accumulated, suggesting an inhibition of the 3-keto reductase involved in C-4 demethylation. Thus, fenhexamid belongs to a new, promising class of sterol biosynthesis inhibitors not previously used in agriculture or in medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 29 publications
2
66
0
3
Order By: Relevance
“…Effect of two consecutive applications of 40 g 100 L -1 isofetamid and 37.5 g 100 L -1 fenhexamid, applied at critical growth stages of grapevine for gray mold (Botrytis cinerea) control. an ergosterol biosynthesis inhibitor widely used to control grape mold (Debieu et al, 2001). Both fungicides prevented gray mold development on grapevines by reducing B. cinerea at flowering and arresting gray mold infection at harvest time.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of two consecutive applications of 40 g 100 L -1 isofetamid and 37.5 g 100 L -1 fenhexamid, applied at critical growth stages of grapevine for gray mold (Botrytis cinerea) control. an ergosterol biosynthesis inhibitor widely used to control grape mold (Debieu et al, 2001). Both fungicides prevented gray mold development on grapevines by reducing B. cinerea at flowering and arresting gray mold infection at harvest time.…”
Section: Discussionmentioning
confidence: 99%
“…Although biological control of fungal growth is becoming popular on account of environmental concerns (Elmer & Reglinski 2006), generally B. cinerea infections are prevented by the application of fungicides. Fenhexamid, a hydroxanilide derivative, is one of the newly developed fungicides that exhibit strong inhibitory activity against B. cinerea, owing to its ability to inhibit 3-ketoreductase in the C4-demethylation enzyme complex during ergosterol biosynthesis (Rosslenbroich et al 2000;Debieu et al 2001). Fenhexamid is used in many European countries and is considered to be an effective fungicide against B. cinerea due to its unique mode of action (Rosslenbroich et al 2000;Debieu et al 2001;Baroffio et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…After the initiation of spore germination the fenhexamid inhibit the germ-tube elongations, germtubes collapse and die before they are able to penetrate plant surface. Also, treated hyphae frequently show a characteristic leakage of cytoplasm or cell wall associated material at the hyphal tip area (Haenssler & Pontzen, 1999;Debieu et al, 2001). It is sterol biosynthesis inhibitor and blocks the C4-demethylations (Rosslenbroich & Stuebler, 2000).…”
Section: Managing Grey Mouldmentioning
confidence: 99%
“…Owing to its novel mode of action, differing from all other botryticides it was presumed that resistance to fenhexamid will not occur easily. Analyses of unsaponifiable compounds conducted by Debieu et al (2001) revealed that fenhexamid inhibited sterol biosynthesis in B. cinerea. The major sterol constitutes in B. cinerea, as well as in most filamentous fungi, is ergosterol.…”
Section: Retrospective Of Botryticide Resistancementioning
confidence: 99%
See 1 more Smart Citation